" … I felt completely stranded": liminality and recognition of personhood in the experiences of suicidal women admitted to psychiatric hospital. Issue 1 (1st January 2020) - Hagen, Julia; Loa Knizek, Birthe; Hjelmeland, Heidi
ABSTRACT: Purpose : The purpose of this study is to explore how patients experience their suicidality and how they experience being in a psychiatric hospital. Methods : This is part of a field study, and the article is based on data collected in interactions with 11 women who were admitted to a psychiatric hospital and were struggling with suicidality. Data were collected through interviews, conversations, and participatory observation. We analysed the data by means of Systematic Text Condensation, followed by a deductive process where the data and preliminary findings were interpreted in light of the theory of liminality. Results : We found that the patients' experiences of suicidality and being a patient in a psychiatric acute ward involve "Liminality and weakened sense of personhood, " and from their perspective, "Recognition of personhood" is an important aspect of care. Conclusion : Our study indicates that suicidality and psychiatric hospitalization involve liminality and weakened sense of personhood, aspects that are important to consider in the care of the patients. Professionals need to acknowledge more the importance of recognition of personhood in care, since this can strengthen the patient's self-worth and empower the person. Lack of recognition may increase the patient's suffering and suicidality.